Postbiotics: Metabolites and mechanisms involved in microbiota-host interactions - Peluzio, Maria do Carmo Gouveia; Martinez, J. Alfredo; Milagro, Fermin I. (Trends in food science & technology, 2021)
The knowledge on the mechanisms through which the metabolites produced by the gut microbiota (postbiotics) prevent diseases, induce therapeutic responses, and behave differently in response to dietary and environmental changes, is one of the major challenges in nutrition research and paves the route for the development of new therapeutic strategies against non-communicable diseases. In this review, the main mechanisms by which postbiotics provide a link between nutrition, microbiota, and human health are discussed. Postbiotics are the repertoire of metabolites produced in the fermentation process of dietary components (mainly fibers and polyphenols, but also complex carbohydrates, proteins, and lipids), as well as the endogenous components generated by bacteria-host interactions that influence human health. Short-chain fatty acids denote a primary energy source for colonocytes, also acting on the gut-brain axis to reduce appetite and performing epigenetic roles. Polyamines promote homeostasis and affect epigenetic processes, apoptosis, and cell proliferation through interaction with proteins and nucleic acids. Bile acids are involved in glucose metabolism and modulation of the host immune response. p-Cresol features antimicrobial and antioxidant properties, but has been related to enteric pathogens, autism, and kidney diseases. The role of trimethylamine N-oxide (TMAO) in cardiovascular diseases is still under debate. Bacteriocins have antibiotic action against pathogens. The beneficial effects of polyphenols are demonstrated by their essentiality in the production of metabolites. Summarizing, metagenomic sequencing, intervention studies, and metabolomics are enabling to understand the modulation and effects of microbiota metabolic activity. However, in order to clearly elucidate the food-microbiota axis, the interplay among the host microbiota and the metabolites secreted by intestinal cells, and the intestine-liver-brain axis, the studies must be directed to the subject habitat. •Postbiotics provide therapeutic benefits, preserve the integrity and improve the balance of the host microbiome.•Iron, calcium, phosphorus, and zinc are dependent on bacteria for the processes of absorption and/or maintenance in the body.•Bacteriocins from lactic acid bacteria have low or no cytotoxicity,can inhibit the growth of enteropathogenic bacteria.•Postbiotics are involved in the regulation of the immune, neurological, and physiological systems.